Perspectives on the Treatment of Advanced Thyroid Cancer: Approved Therapies, Resistance Mechanisms, and Future Directions - Porter, Ashleigh; Wong, Deborah J. (Frontiers in Oncology, 2021)
For differentiated thyroid cancer (DTC), systemic therapy with radioactive iodine (RAI) is often utilized for radiosensitive disease, while for radioiodine refractory (RAIR) disease, current standard of care is treatment with multikinase tyrosine kinase inhibitors (TKI). For BRAF-mutant DTC or anaplastic thyroid cancer (ATC), treatment with inhibitors targeting BRAF and MEK are important advances. RET-inhibitors for RET-mutated medullary thyroid cancer recently have been FDA-approved for metastatic disease. Nevertheless, treatment of thyroid cancer resistant to current systemic therapies remains an important area of need. Resistance mechanisms are being elucidated, and novel therapies including combinations of BRAF and MEK inhibitors with RAI or other targeted therapies or TKIs combined with checkpoint inhibition are current areas of exploration.